2020
DOI: 10.2147/dddt.s253405
|View full text |Cite
|
Sign up to set email alerts
|

<p>Soluplus-Mediated Diosgenin Amorphous Solid Dispersion with High Solubility and High Stability: Development, Characterization and Oral Bioavailability</p>

Abstract: Background and Purpose The traditional Chinese medicine, diosgenin (Dio), has attracted increasing attention because it possesses various therapeutic effects, including anti-tumor, anti-infective and anti-allergic properties. However, the commercial application of Dio is limited by its extremely low aqueous solubility and inferior bioavailability in vivo. Soluplus, a novel excipient, has great solubilization and capacity of crystallization inhibition. The purpose of this study was to prepare Solup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…GB peaks at 1089.82 (shifted to 1091-6) and 1529 (shifted to 1531-2) cm and the polymer interaction was an extra advantage for the nanomicelles. Not only inhibit the crystallization of the drug but improved the solid solubility of the drug into the hydrophilic matrix [33]. The results were consistent with the drug release results.…”
Section: Ftir Analysis Supported By Chemometric Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…GB peaks at 1089.82 (shifted to 1091-6) and 1529 (shifted to 1531-2) cm and the polymer interaction was an extra advantage for the nanomicelles. Not only inhibit the crystallization of the drug but improved the solid solubility of the drug into the hydrophilic matrix [33]. The results were consistent with the drug release results.…”
Section: Ftir Analysis Supported By Chemometric Analysissupporting
confidence: 86%
“…Observed peaks at 1159.26, 1184.33 cm -1 and distinct sharp peaks at 1305.85, 1344.43 cm -1 are correlated with the asymmetric and symmetric stretching vibration of SO 2 [22]. The urea N-H stretching vibrations are found at 1274.99, 1620. , and C-O-C stretching at 1471.74 cm -1 [33,34]. The FTIR spectra of physical mixtures were similar to the pure GB and the individual polymer spectra, which strongly void the chemical interaction.…”
Section: Ftir Analysis Supported By Chemometric Analysismentioning
confidence: 92%
“…Due to the poor water solubility and strong hydrophobicity of diosgenin, its oral bioavailability is not ideal, and numerous diosgenin formulation strategies have been applied to overcome these issues, including liquid crystalline (LCs) and b-cyclodextrin (b-CD) complexes, nanocrystals, and soluplus-mediated diosgenin Amorphous Solid Dispersion (ASD) technology. 103 , 104 In recent decades, ASDs have been the subject of increased research interest, as they can increase the oral bioavailability of poorly soluble drugs. 105 The aqueous solubility of optimized ASDs was significantly improved due to the amorphization of diosgenin and the molecular interactions between diosgenin and soluplus.…”
Section: Advantages and Limitations Of Diosgeninmentioning
confidence: 99%
“…Hence, diosgenin ASDs, with their high solubility, high bioavailability, and high stability, represent a promising route toward pharmaceutical applications. 104 Simultaneously, although numerous preclinical studies have demonstrated that diosgenin has reliable lipid metabolism regulation function, clinical research data remain limited. Therefore, it will be necessary to verify the therapeutic effects of diosgenin on human hyperlipidemia via additional clinical trials in the future.…”
Section: Advantages and Limitations Of Diosgeninmentioning
confidence: 99%
“…Positive effect of factor A was fond on solubility, as solubility enhanced with the increase in concentration of Soluplus, which may be designated to hydrophilic nature of compound. Enhanced concentration of this carrier may impart more hydrophilicity and reduced crystallinity of the drug there by enhancing solubility of Ritonavir (Liu et al, 2020). Factor B also exerted positive effect on the initial solubility, S0.…”
Section: Solubilitymentioning
confidence: 99%